DNA‐Based Biomaterials for Immunoengineering. Issue 4 (5th December 2018) - Maeda, Midori; Kojima, Taisuke; Song, Yang; Takayama, Shuichi
Abstract: Man‐made DNA materials hold the potential to modulate specific immune pathways toward immunoactivating or immunosuppressive cascades. DNA‐based biomaterials introduce DNA into the extracellular environment during implantation or delivery, and subsequently intracellularly upon phagocytosis or degradation of the material. Therefore, the immunogenic functionality of biological and synthetic extracellular DNA should be considered to achieve desired immune responses. In vivo, extracellular DNA from both endogenous and exogenous sources holds immunoactivating functions which can be traced back to the molecular features of DNA, such as sequence and length. Extracellular DNA is recognized as damage‐associated molecular patterns (DAMPs), or pathogen‐associated molecular patterns (PAMPs), by immune cell receptors, activating either proinflammatory signaling pathways or immunosuppressive cell functions. Although extracellular DNA promotes protective immune responses during early inflammation such as bacterial killing, recent advances demonstrate that unresolved and elevated DNA concentrations may contribute to the pathogenesis of autoimmune diseases, cancer, and fibrosis. Therefore, addressing the immunogenicity of DNA enables immune responses to be engineered by optimizing their activating and suppressive performance per application. To this end, emerging biology relevant to the generation of extracellular DNA, DNA sensors, and its role concerning existing and future synthetic DNA biomaterials are reviewed. Abstract : Recent advances in extracellular DNA biology present new opportunities for DNA‐based biomaterial design with tuned immune responses. The manner in which DNA interacts with immune cells, the sources of extracellular DNA, and finally, the emerging biotechnologies that incorporate DNA molecules is also described. Leveraging the immunomodulatory capacity of DNA enables tailored materials that prime specific immunoactivating or immunosuppressive outcomes.